Profil uczennicy w wizji i ocenie założycielek Szkoły Domowej Pracy Kobiet - Biniaś-Szkopek, Magdalena; Wesołowska, Julia (Biuletyn Historii Wychowania, 2024)
Women’s Household Work School (Kórnicki Institute) was founded by Jadwiga Zamoyska on 24 July 1884 in Kórnik. Its mission was to educate young girls in housewife’s chores, including both physical work (cleaning, laundering, cooking) and running the household in terms of accounting, managing servants, etc. Great emphasis was placed on in-depth studies of the catechism and the Bible. Nevertheless, the Institute was a secular organisation which did not force its participants to take religious vows. That is why it remains one of the most exceptional places in the late 19th and the early 20th centuries where dozens of young women were taught Zamoyska’s original method of education. The aim of the thesis is to present an evolution of the vision of the students created by the school’s founders and to depict the female students. The basis of the publication are memoirs by Maria Zamoyska and the teachers’ correspondence from 1882 to 1923.